2018
DOI: 10.22146/ijc.26783
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Cellulase Activity Test and Molecular Identification of Selected Cellulolytic Bacteria Indigenous Rice Bran

Abstract: Rice bran is the waste product of rice milling which is abundant in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The stationary growth phase of cellulolytic bacteria occurred from 24 h until 64 h for A1D, A1I, A2A, and B1A, then followed by the death phase at 72 h, whereas A1E and A1K still in the stationary growth phase at 72 h. In the stationary growth phase, there is a balance between the number of live cells and dead cells [23]. Each bacterial isolate with a density of 10 7 cells.mL -1 at exponential growth phase (24 h incubation) had the highest potency for the production of cellulase enzymes A similar study showed the exponential growth phase of cellulolytic bacteria occurs at 4 -24 h incubation [13]. Another research was reported that the production of cellulase enzymes at 24 h incubation [24].…”
Section: Growth Curve Of Selected Cellulolytic Bacteriamentioning
confidence: 83%
See 3 more Smart Citations
“…The stationary growth phase of cellulolytic bacteria occurred from 24 h until 64 h for A1D, A1I, A2A, and B1A, then followed by the death phase at 72 h, whereas A1E and A1K still in the stationary growth phase at 72 h. In the stationary growth phase, there is a balance between the number of live cells and dead cells [23]. Each bacterial isolate with a density of 10 7 cells.mL -1 at exponential growth phase (24 h incubation) had the highest potency for the production of cellulase enzymes A similar study showed the exponential growth phase of cellulolytic bacteria occurs at 4 -24 h incubation [13]. Another research was reported that the production of cellulase enzymes at 24 h incubation [24].…”
Section: Growth Curve Of Selected Cellulolytic Bacteriamentioning
confidence: 83%
“…The crude enzyme was obtained by centrifugation of culture medium at 4°C, 10.000 rpm for 10 minutes. The supernatant was defined as a crude cellulase enzyme [13].…”
Section: Growth Curve and Crude Enzyme Production Of Selected Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…The solution was cooled for 20 min and the absorbance was measured using a spectrophotometer at 540 nm. One activity unit (U/mL) is expressed as the total amount of reduced sugars (1000 μmoL) in the reaction mixture per 30 min [11,12].…”
Section: Cellulase Assaymentioning
confidence: 99%